Characterization of traps in GaN-based HEMTs by drain voltage transient and capacitance deep-level transient spectroscopy. (1st September 2022) - Pan, Shijie; Feng, Shiwei; Li, Xuan; Bai, Kun; Lu, Xiaozhuang; Zhang, Yamin; Zhou, Lixing; Rui, Erming; Jiao, Qiang; Tian, Yu
Abstract: This paper presents a detailed investigation of trapping effect in AlGaN/GaN high-electron-mobility transistors based on the pulsed current–voltage characterization, drain voltage transient (DVT) measurement, and capacitance deep-level transient spectroscopy (C-DLTS). By monitoring the DVTs at various filling voltages and temperatures, the properties of three electron traps were obtained with the DVT measurements. Specifically, the energy levels of the former two traps were determined to be 0.28 and 0.48 eV, which was confirmed by the C-DLTS measurement performed on the same device. In addition, a third temperature-independent trap located in the GaN buffer was observed only with the DVT measurement, indicating the advantage of transient curves measurement in characterizing the traps insensitive to temperature. The combined measurements demonstrate the correlation of different techniques, which allows identifying the same trap levels to investigate the physical origin of traps.